Ontic or epistemic conception of explanation: A misleading distinction? - Oleksowicz, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
In this paper, I discuss the differences between ontic and epistemic conceptions of scientific explanation, mainly in relation to the so-called new mechanical philosophy. I emphasize that the debate on conceptions of scientific explanation owes much to Salmon’s ontic/epistemic distinction, although much has changed since his formulations. I focus on the interplay between ontic and epistemic norms and constraints in providing mechanistic explanations. My conceptual analysis serves two aims. Firstly, I formulate some suggestions for recognising that both sets of norms and constraints, ontic and epistemic, are necessary for scientific theorising. Secondly, I emphasize that there are multiple dimensions involved in scientific explanation, rather than clear-cut alternatives between ontic and epistemic aspects. I conclude with a general observation that although contextual aspects of explanations are unavoidable, the epistemic-relativity of our categories, explanations and models can in fact be compatible with their objectivity. Instead of making hastily drawn ontological implications from our theories or models, we should carefully scrutinize them from the ontic-epistemic perspective.
Keywords: new mechanical philosophy; mechanistic explanation; ontic; epistemic; explanatory norms; explanatory constraints